Fucoidan-containing microcapsules formed on different matrices with the use of the maillard reaction - Viktoria Evgen'evna Suprunchuk; Evgenija Vladimirovna Denisova (Наука. Инновации. Технологии)
In this paper, we investigate the possibility of forming multi-layered microcapsules containing fucoidan on matrices of different nature. As carriers was used vaterite meso-porous CaCO3 particles and polystyrene particles. As biopolymers have been used fucoidan and bovine serum albumin (BSA). Measuring the size of the obtained microcapsules was carried out using the method of dynamic light scattering (DLS) and scanning probe microscopy (SPM). Optical microscopy and SPM was used to establish the shape of the microcapsules. The work has also identified conditions for the formation of microcapsules with the use of the Maillard reaction and the dependence of the size of the microcapsules of the nature of the media.